Prenatal diagnosis of complete penoscrotal transposition with normal scrotum: Two case reports and review of the literature. Issue 6 (22nd April 2020) - Kurt, Didar; Sivrikoz, Tuğba Saraç; Kalelioğlu, Halil İbrahim; Has, Recep; Ziylan, Hasan Orhan; Yüksel, Atıl
Abstract: Complete penoscrotal transposition is an extremely rare congenital anomaly and is usually associated with other urinary system abnormalities. Prenatal diagnosis is feasible by demonstrating perineal anatomy and its relation with scrotum and phallus. We describe two prenatal cases presenting with oligohydramniosis and megacystis due to lower urinary tract obstruction. Postnatal diagnosis was confirmed in both cases. Considering the dismal perinatal outcome, an accurate prenatal diagnosis is required for counseling the parents and preparing for postnatal care.